Tesla, Inc.: the new era of tesla - Henriques, Ricardo João Freitas (2020)
The aim of this equity research is to provide a comprehensive valuation and analysis of Tesla Inc, containing a final recommendation indicating which investment opportunity is the most appropriate and advisable, to buy, hold or sell the company's stock.We valuedTesla in three business segments(Transportation, Energy Generation and Energy Storage)using Discounted Cash Flow (DCF)model.